Influence of shunting of high-temperature strain gaugers on the accuracy of measuring static deformations of GTE elements - Yuriy Husyev; Anatoliy Hol'tsov; Serhiy Kryhin (Авіаційно-космічна техніка та технологія, 2022)
The development of gas turbine engines (GTE), for various purposes, is inextricably linked with an increase in their main characteristics. Simultaneously, the parameters of the working fluid increase, in particular, the temperature of the gas flow and the intensity of loads on structural elements with an increasing frequency of rotation of the rotors. The strength reliability of highly heated GTE elements is a factor that determines the life of the engine as a whole. The most common cases of damage to GTE elements are caused by static stresses, and mainly relate to the blade apparatus, compressor and gas turbine housings, combustion chambers and rotor elements operating in the temperature range of 200–750 °C. Errors in measuring static deformations of parts are usually associated with insufficient compensation for the temperature increment of resistance by the sensitive element (SE) of the strain gauge and with the occurrence of shunt currents between the SE and the body of the part through a binder insulator. The change in the electrical resistance of the strain gauge SE is perceived by the measuring system as an imaginary deformation. The measurement error due to shunting increases significantly with an increase in the temperature of the part under study, since this significantly reduces the specific electrical resistance of the binder insulator. A strain gauge sensor with two sensitive elements is considered in this work. The lower CE of the strain gauge sensor is located in the insulator-connector directly in the vicinity of the body of the part and perceives its main deformation. The upper Euro is located above the lower. The main axes of the elements are rotated relative to each other by 90 ° C and plays the role of temperature-compensating element and at the same time registers the transverse deformation of the part. An electrical model of the potential distribution in a strain gauge is presented. To determine the magnitude of shunt currents, Kirchhoff's rule was applied to a linear electric circuit, and finite-difference differential equations for the sum of currents in all nodes of the electric model were recorded. Finite-difference differential equations are transformed into a matrix one, the solution of which allows to obtain leakage currents in all nodes of the electric model of the strain gauge. The total leakage currents in the lower and upper SE strain gauge for different cases, as well as the relative errors of deformation measurement due to shunting, are obtained.